Association between Physics Engineering Laboratory Comfort and Sick-Building Syndrome of Universitas Multimedia Nusantara Student - Nicholas Pranata (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2024)
Humans spend most of their time doing activities inside a room. Room comfort becomes one of the important factors to support human activities. The lack of comfort can trigger sick-building syndrome for room occupants which leads to nausea, irritation, loss of concentration and other types of sickness. Thus, a study is conducted in the Physics Engineering laboratorium to measure the physical comfort based on temperature, relative humidity, and illuminance using CEM DT-8820 environment meter. A quantitative descriptive method is used. In addition, a survey is made to collect sick-building syndrome occurrence data by laboratorium occupants. It is obtained that temperature is lower than 24?-27?, relative humidity in accordance (by 55% - 56%) and illuminance under 500 lux as the standard for laboratory. Based on questionnaire results, sick-building syndrome that appears on respondents are dry throat by 23,3%, dry lips by 40,0%, drowsiness by 66,7%, poor concentration by 33,3%, etc. which correlates to temperature by -0,0156 (very low negative correlation), relative humidity by -0,1297 (low negative correlation) and illuminance by -0,4393 (moderate negative correlation).